2011
DOI: 10.3892/or.2011.1133
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 protein, mRNA expression and T19007C polymorphism as prognostic markers in head and neck squamous cell carcinoma patients treated with surgery and adjuvant cisplatin-based chemoradiation

Abstract: Abstract. Adjuvant cisplatin-based chemoradiation improves survival in HNSCC patients presenting with risk features. ERCC1 (excision repair cross-complementation group 1) is associated with resistance to chemo-and radiation therapy and may have a prognostic value in HNSCC patients. Here we studied ERCC1 expression and the polymorphism T19007C as prognostic markers in these patients. This is a retrospective and translational analysis, where ERCC1 protein expression was evaluated by immunohistochemistry, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 37 publications
1
16
2
2
Order By: Relevance
“…In our cohort of patients, the persistent positive predictive role of ERCC1 for OS can be explained by the use of platinum-based chemotherapy for recurrent inoperable or metastatic disease (data not shown). Our results are in contrast to those published by De Castro et al [14] that demonstrated a better prognosis for HNSCC patients with high ERCC1 expression submitted to adjuvant cisplatin-based chemotherapy. Even though in the two studies the antibody and the IHC scoring systems were the same, the ERCC1 expression described by De Castro et al was low (54%) compared to our results and other reports [10,11].…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…In our cohort of patients, the persistent positive predictive role of ERCC1 for OS can be explained by the use of platinum-based chemotherapy for recurrent inoperable or metastatic disease (data not shown). Our results are in contrast to those published by De Castro et al [14] that demonstrated a better prognosis for HNSCC patients with high ERCC1 expression submitted to adjuvant cisplatin-based chemotherapy. Even though in the two studies the antibody and the IHC scoring systems were the same, the ERCC1 expression described by De Castro et al was low (54%) compared to our results and other reports [10,11].…”
Section: Discussioncontrasting
confidence: 56%
“…An explanation could be that the positive prognostic role of high ERCC1 expression can be counterbalanced by its negative predictive activity, confirming the hypothesis and interpretation on the opposite and not additive role of high ERCC1 expression formulated by others [12]. De Castro et al [14] reported low 5-year OS and DFS rates compared to our study as well as to the EORTC and RTOG studies, and it was explained by a very long median overall treatment time (21 weeks). This recognition might suggest population heterogeneity between the two studies, which makes the results less comparable.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations